In vitro Propagation and Callus Formation of Bacopa monnieri (L.) Penn. - Showkat, Patni; Zaidi, Yaseer; Asghar, Suhail; Jamaluddin, Shamsuddin (Plant Tissue Culture and Biotechnology, 2011)
An important medicinal herb, namely Bacopa monnieri (L.) Penn. showed best results on MS with 1 mg/l IAA and 1 mg/l IBA for culture initiation, multiple shoot proliferation, bud breakage, shoot length, shoot numbers and cluster formation. For rooting the best result was obtained on MS solidified with 7 g/l of agar along with sugar 20 gm/l for root, shoot ratio and number of roots. The best hardening was achieved in a mixture of soil : soilrite (1 : 1) where the survival rate was 94%. Further, for callus formation the best result was obtained in the leaf explants on MS supplemented with 0.5 mg/l 2, 4-D. HPLC and HPTLC profile of regenerated shoots revealed a phytochemicals profile similar to that of the market samples and mother plants. The presence of bacoside was detected through HPTLC and HPLC. Key words: Bacopa monnieri, Micropropagation, Bacoside D.O.I. 10.3329/ptcb.v20i2.6890 Plant Tissue Cult. & Biotech. 20(2): 119-125, 2010 (December)